Penghuni Gua As-Habul Kahfi Kisah Para Remaja Yang Beriman Membaja Tertidur 309 Tahun - Ahmad Baraniq (PT Bulan Bintang, 2002)
Penghuni Gua As-Habul Kahfi Kisah Para Remaja Yang Beriman Membaja Tertidur 309 Tahun